ANALYSIS INDICATOR OF FACTORS AFFECTING HUMAN DEVELOPMENT INDEX (IPM) - Windya Wahyu Lestari; Victoria Efrida Sanar (Geosfera Indonesia, 2018)
The purpose of this study is to determine how big the influence of the indicators of factors that affect the Human Development Index. In addition, to determine the relationship of indicators of factors that affect the Human Development Index, to determine the development of human development of variables. That way can provide a standard against a State in improving the quality of human resources. Using the SPSS application method, this paper found that the variables that significantly influence the indicators of factors affecting the Human Development Index are life expectancy index, education index and income index. The estimation result using Correlasion Pearson shows that 14.788% is the variation of each observation is the same. Keywords : Human Development Index, Life Expectancy Index, Education Index, Revenue Index. Copyright (c) 2018 Geosfera Indonesia Journal and Department of Geography Education, University of Jember Copyright Notice This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License